The Impact of Audit Committee Characteristics on Financial Distress - Wiryaningrum, Mutiara Sukma; Januarti, Indira; Rosa, Adelia (E-Jurnal Akuntansi, 2025)
This research to analyze impact of audit committee characteristics on financial distress, which could be seen from size, independent, meetings frequency, educational background and gender diversity of the audit committee. The study applies Springate Model and categorize financial of the company in two conditions, company which occurs financial distress and company has good financial (healthy company). Using manufacturing company listed on IDX period 2017-2023 as a population of the research. Final samples in this study are 920 samples, consist of 461 samples occurs financial distress and 459 samples in healthy financial condition. Analysis data used logistic regression. Results of this research showed that size, independent and educational background of audit committee has negative impact on financial distress. Whereas meetings frequency audit committee has positive impact on financial distress and audit committee gender diversity has no impact on financial distress. Keywords: Financial Distress; Audit Committees; Springate Model